La normalización historiográfica y la pérdida de la inocencia. Reflexiones acerca de algunas tesis del historiador Santos Juliá / Historiographical Standardization and the Loss of Innocence. Reflections on some Theses of the Historian Santos Juliá - Cuesta Fernández, Raimundo (Historiografías, 2017)
This article develops the author’s contribution to the panel at the public presentation of the book Hoy no es ayer. Ensayos sobre la España del siglo (Barcelona, RBA, 2010), a compilation of essays by professor Santos Juliá. The event, held on 5 March 2015 at one of the regular sessions of Current Spain debate seminars at the auditorium of the Faculty of Philosophy and Arts in the University of Salamanca (Spain), had the attendance of the author of the book. The paper aims at interpreting and reviewing from a critical perspective some of his main ideas about whether or not the Spanish route to modernity was normal, and discusses his positive assessment of the Spanish transition as well as his views on the relationships between history and memory. Key Words Modernization, Transition, history, memory, historical memory, historiographical standardization. Resumen Este artículo desarrolla la intervención del autor en el acto de presentación del libro recopilatorio de Santos Juliá, Hoy no es ayer. Ensayos sobre la España del siglo XX (Barcelona: RBA, 2010), dentro de una de las sesiones del Aula de Debate La España Actual, celebrada en el salón de actos de la Facultad de Historia de la Universidad de Salamanca (España), el 5 de marzo de 2015, que contó con la asistencia del autor del libro. En el texto se realiza una interpretación y revisión crítica de algunas de sus ideas sobre la normalidad de la vía española hacia la modernidad, de sus valoraciones positivas sobre el proceso de la Transición y, finalmente, de su concepción acerca las relaciones entre historia y memoria. Palabras clave Modernización, Transición, historia, memoria, memoria histórica, normalización historiográfica.